Identification and characterization of mcr mediated colistin resistance in extraintestinal Escherichia coli from poultry and livestock in China. Issue 24 (8th November 2017) - Yassin, Afrah Kamal; Zhang, Jilei; Wang, Jiawei; Chen, Li; Kelly, Patrick; Butaye, Patrick; Lu, Guangwu; Gong, Jiansen; Li, Min; Wei, Lanjing; Wang, Yaoyao; Qi, Kezong; et al.
Abstract: Antimicrobial resistance to colistin has emerged worldwide threatening the efficacy of one of the last-resort antimicrobials used for the treatment of multidrug-resistant Enterobacteriacea e infection in humans. In this study, we investigated the presence of colistin resistance genes ( mcr-1, mcr-2, mcr-3 ) in Escherichia coli strains isolated from poultry and livestock collected between 2004 and 2012 in China. Furthermore, we studied the maintenance and transfer of the mcr-1 gene in E. coli after serial passages. Overall, 2.7% (17/624) of the E. coli isolates were positive for the mcr-1 gene while none were positive for the mcr-2 and mcr-3 genes. The prevalences of mcr-1 were similar in E. coli isolates from chickens (3.2%; 13/404), pigs (0.9%; 1/113) and ducks (6.8%; 3/44) but were absent in isolates from cattle (0/63). The mcr-1 gene was maintained in the E. coli after six passages (equivalent to 60 generations). In vitro transfer of mcr-1 was evident even without colistin selection. Our data indicate the presence of mcr-1 in extraintestinal E. coli from food-producing animals in China, and suggest that high numbers of the mcr-1 -positive bacteria in poultry and livestock do not appear to be readily lost after withdrawal of colistin as a food additive. Abstract : This study indicates the presence of mcr-1 in extraintestinal Escherichia coli in livestock in China, and the mcr-1 -positive bacteria do not appear to be readily lost after colistin withdrawal.